Student’s research activities: assessment of individual achievements - YU. P. Gospodarik (Высшее образование в России)
The article raises the problem concerning such an important element of student’s research work as accounting and publishing its results. The modern era of digital technology not only makes high demands to the content of student research papers, but also opens opportunities to create a new system of registration and publication. The article explains the importance of assessment of individual student achievements in scientific research.